Pharmacy students’ knowledge and perceptions about Pharmacovigilance in Malaysian public universities - Mahmod El-Kalmi, Ramadhan Mohamed; Hassali, Mohamed Azmi; Mohamed Ibrahim, Mohamed Izham; Widodo, Riyanto Teguh; Al-Efan, Qais Muhammad Ahmad; Abdul Hadi, Muhammad (American Association of Colleges of Pharmacy (AACP), 2011)
Objective. To assess senior pharmacy students’ knowledge of and perceptions about pharmacovigilance and reporting of adverse drug reactions (ADRs) at 5 public universities in Malaysia Methods. A cross-sectional study was conducted between December 1, 2010, and January 31, 2010, using a validated self-administered questionnaire delivered to a sample of 510 final-year (fourth-year) pharmacy students at 5 Malaysian public universities. Results. Four hundred twenty-one (84%) students responded to the survey. About 60% (n 5 240) indicated that they had taken courses on the concept of pharmacovigilance during their current pharmacy curriculum. The mean score for knowledge about pharmacovigilance and ADR reporting was 6.961.4. There was a significant difference in the mean scores for knowledge about pharmacovigilance across the 5 universities. The majority (82.3%) of respondents felt it was necessary to confirm the causal relationship between the drug and the ADR. About 57.8% (n 5 241) of the respondents believed that pharmacy students are competent and capable of reporting ADRs during their clerkships. The majority (87.0%) of respondents perceived that pharmacy students should be taught how to report ADRs. Conclusion. The results of this study demonstrate that the majority of final-year pharmacy students in Malaysian public universities have insufficient knowledge about pharmacovigilance and ADR reporting